2017
DOI: 10.1007/s12253-017-0249-8
|View full text |Cite
|
Sign up to set email alerts
|

Tumor LXR Expression is a Prognostic Marker for Patients with Hepatocellular Carcinoma

Abstract: Liver X receptor (LXR) activation exerts an anti-tumor effect. However, whether the tumor LXR expression has prognostic significance in hepatocellular carcinoma (HCC) patient has not been addressed yet. Primary HCC and the adjacent non-tumor tissues were obtained from 169 patients who underwent routine curative surgical treatment. All patients were followed for prognosis analyses. Tumor LXR was detected by immunohistochemical analysis. In in vitro study, several HCC cell lines were cultured for cellular protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…In summary, we found that LXR agonists can enhance the activity of sorafenib in killing HCC. This result stems from our in vivo data demonstrating that Nr1h3 cDNA (encoding LXR) is incompatible with the growth of MYC-driven tumors in the presence of sorafenib, and fits well with a recent study noting a correlation between LXR expression and improved HCC survival 31 . Furthermore, another publication compared the expression patterns of sorafenib-sensitive and resistant human HCC cell lines, 38 and their data showed a significantly decreased level of LXRα expression in sorafenib-resistant cells (p < 0.01).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In summary, we found that LXR agonists can enhance the activity of sorafenib in killing HCC. This result stems from our in vivo data demonstrating that Nr1h3 cDNA (encoding LXR) is incompatible with the growth of MYC-driven tumors in the presence of sorafenib, and fits well with a recent study noting a correlation between LXR expression and improved HCC survival 31 . Furthermore, another publication compared the expression patterns of sorafenib-sensitive and resistant human HCC cell lines, 38 and their data showed a significantly decreased level of LXRα expression in sorafenib-resistant cells (p < 0.01).…”
Section: Discussionsupporting
confidence: 91%
“…A potential concern with using LXR agonists is increased fatty acid synthesis and hepatic steatosis upon LXR activation 30 . However, HCC patients with increased LXR expression have better prognosis than those with lower expression 31 , suggesting that activating LXR with an agonist is a plausible treatment option. LXR expression has been found to be upregulated in various adenocarcinomas, as compared to squamous cell carcinomas from the same tissues of origin 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we for the first time revealed that LXR downregulated HULC by repressing its gene promoter activity, leading to the growth inhibition of HCC cells. Besides HCC, LXR and HULC are also associated with other cancers such as breast cancer, prostate cancer, ovarian cancer and colorectal cancer [11][12][13][14][15][16][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that LXR plays important roles in regulating the metabolisms of glucose, lipid and cholesterol by binding to LXR response elements (LXREs) of its targeting genes [9,10]. Interestingly, the recent studies have revealed that LXR exerts anti-tumor effects on various cancers such as HCC, breast cancer, prostate cancer, ovarian cancer, and colorectal cancer [11][12][13][14][15][16], suggesting that LXR is a potential target in cancer treatment. However, it is not well known about the mechanisms by which LXR plays its anti-tumor function, especially, it is unclear whether the anti-HCC effect of LXR is involved in the regulation of HULC.…”
mentioning
confidence: 99%
“… 17 - 19 Recently, accumulating evidence demonstrated that LXR was a potential prognostic marker and exerted significant anti-tumor effect in HCC. 20 , 21 Furthermore, many genes related with cell proliferation (FOXM1, SOCS3), invasion, and migration in HCC are directly regulated by LXR. 22 - 24 However, limited knowledge is available concerning whether LXR affects the proliferation of HCC cells by modulating miR-124-3p, which needs to be studied further.…”
Section: Introductionmentioning
confidence: 99%